A new record of Anemopaegma (Bignoniaceae, Bignonieae) for Mexico - Hernández-Esquivel, Karen Beatriz; Sánchez-Ortiz, Wilber; Damon, Anne (Instituto de Ecología, A.C., 2023)
Background and Aims: The genus Anemopaegma comprises 45 Neotropical species. The most recent literature has three of them registered for Mexico. A fourth species of this genus was identified in the living plant collection of the Jardin Etnobiológico de las Selvas del Soconusco (JESS) and collected from the area surrounding the garden. There has been no confirmed record of this species for Mexico. The aim of this study was to register more collections of this species in the field, in databases and herbaria, to describe its characteristics and generate a key to identify the Anemopaegma species in Mexico. Methods: Field trips were carried out in the area surrounding the JESS to locate wild populations of Anemopaegma. Sterile and fertile material was collected from the studied individuals and deposited in the ECO-TA-H and MEXU herbaria. Herbarium specimens of the genus Anemopaegma were reviewed in the National Herbarium of Mexico (MEXU), and databases were consulted to see records in other herbaria. Key results: The record of the species Anemopaegma orbiculatum is confirmed for Mexico. Two young individuals were recorded in the wild as well as several seedlings, in addition to the individual from the JESS. These records support the only specimen previously collected whose data are inconsistent. The number of species from this genus in Mexico increases from three to four. An identification key was generated for the Mexican species. Conclusions: The record of few individuals of A. orbiculatum in the field indicates that its presence in Mexico could be threatened, given that the native vegetation of Soconusco, Chiapas, has been strongly impacted. The examination of herbarium specimens provided necessary information to describe the species.